MENGATASI TANTANGAN STUNTING INOVASI DAN KOLABORASI UNTUK MASA DEPAN ANAK INDONESIA - Rose Virgine Tuto Boli; Servia Yosefina Mones; Maria Argensa Dos Santos; Lita Apriani S Haba; Clara D Pio Tae (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
Stunting is a serious health problem that significantly affects child development, especially in Indonesia. This research aims to identify effective innovations and collaboration strategies in addressing the stunting challenge in Indonesia. Using a multidisciplinary approach, this research explores the various factors that cause stunting, ranging from lack of access to nutrition, poor sanitation, to lack of public awareness. In addition, it examines the role of government, non-governmental organizations and the private sector in providing sustainable solutions, such as nutrition education programs, community-based interventions and supporting technologies. The results show that a combination of technological innovation, integrated policies, and cross-sector collaboration can increase the effectiveness of stunting prevention and treatment efforts. Thus, a holistic approach involving all relevant parties is essential to ensure a healthier and more productive future for Indonesian children.